Isolated Fungal Balls in Urinary Bladder Presenting as Acute Retention of Urine. (4th January 2020) - Hameed, Tariq; Jain, Sudhir Kumar; Ansari, Faiz Manzar; Dua, Amrita
Abstract : A 52-year-old male presented to surgery emergency with acute retention of urine. Patient was relieved in the emergency setting by catheterization and bladder irrigation. Urine was sterile; however, microscopy revealed field full of RBCs (>50/high-power field) and pus cells (>20/hpf). Cystoscopy revealed fungal balls in the urinary bladder which upon histopathological examination showed Aspergillus species. Patient was managed with systemic voriconazole and bladder wash with diluted povidone iodine. Predisposing factors diabetes mellitus and benign prostatic hyperplasia were medically managed, and patient recovered well. This case stresses the importance of considering isolated fungal urinary infections in predisposed individuals.